The golden hawks of genghis khan - Ritchie. Rita. (New York : E. P. Dutton & Co., Inc., 1958)
In 1218, disturbing news from a stranger sends the boy, Jalair, eastward to the city of Jenghis Khan in search of the stolen golden hawks.
Includes bibliographical references.
Keywords: y; Mongolia -- Juvenile fiction; Genghis Khan, -- 1162-1227 -- Fiction